Preliminary report of coseismic surface rupture (part) of Türkiye's MW7.8 earthquake by remote sensing interpretation - Yali Guo; Haofeng Li; Peng Liang; Renwei Xiong; Chaozhong Hu; Yueren Xu (Earthquake Research Advances, 2024)
Both MW 7.8 and MW 7.5 earthquakes occurred in southeastern Türkiye on February 6, 2023, resulting in numerous buildings collapsing and serious casualties. Understanding the distribution of coseismic surface ruptures and secondary disasters surrounding the epicentral area is important for post-earthquake emergency and disaster assessments. High-resolution Maxar and GF-2 satellite data were used after the events to extract the location of the rupture surrounding the first epicentral area. The results show that the length of the interpreted surface rupture zone (part of) is approximately 75 ​km, with a coseismic sinistral dislocation of 2–3 ​m near the epicenter; however, this reduced to zero at the tip of the southwest section of the East Anatolia Fault Zone. Moreover, dense soil liquefaction pits were triggered along the rupture trace. These events are in the western region of the Eurasian Seismic Belt and result from the subduction and collision of the Arabian and African Plates toward the Eurasian Plate. The western region of Chinese mainland and its adjacent areas are in the eastern section of the Eurasian Seismic Belt, where seismic activity is controlled by the collision of the Indian and Eurasian Plates. Both China and Türkiye have independent tectonic histories.